Synthesis of an optimal backstepping controller with an adaptive extended observer for missile control systems - Đinh, Hồng Toàn; Le Ngoc Giang; Truong Dang Khoa; Nguyen Cong Dinh (Journal of Military Science and Technology, 2025)
The paper proposes an optimal Backstepping linear quadratic regulator (BLQR) and an Adaptive extended disturbance observer (AEDO) to enhance control performance and disturbance estimation in nonlinear, uncertain systems. The BLQR controller is employed to handle nonlinearities and uncertainties while optimizing control quality, whereas the AEDO effectively estimates and compensates for disturbances in missile control systems. The authors demonstrate system stability based on Lyapunov stability theory and conduct simulations in MatLab/Simulink. The simulation results validate the effectiveness of the proposed approach.